2017
DOI: 10.1016/j.jhevol.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional morphometrics of thoracic vertebrae in Neandertals and the fossil evidence from El Sidrón (Asturias, Northern Spain)

Abstract: Well-preserved thoracic vertebrae of Neandertals are rare. However, such fossils are important as their three-dimensional (3D) spatial configuration can contribute to the understanding of the size and shape of the thoracic spine and the entire thorax. This is because the vertebral body and transverse processes provide the articulation and attachment sites for the ribs. Dorsal orientation of the transverse processes relative to the vertebral body also rotates the attached ribs in a way that could affect thorax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 38 publications
(80 reference statements)
2
25
0
1
Order By: Relevance
“…Recent evidence suggests that the large TLC observed in Neanderthals compared to modern humans was the result of large ribs in the central–lower thorax coupled with a more dorsal orientation of the transverse processes in Neanderthals compared to modern humans, causing mediolateral expansion of the ribcage 18,20 . This ribcage morphology (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that the large TLC observed in Neanderthals compared to modern humans was the result of large ribs in the central–lower thorax coupled with a more dorsal orientation of the transverse processes in Neanderthals compared to modern humans, causing mediolateral expansion of the ribcage 18,20 . This ribcage morphology (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Even though this is just an extrapolation from Schmid's () hypothesis, it would be consistent with results on the bi‐iliac breadth of other authors (Holliday and Hilton, ), who found that Greenland Inuit are the ones that present larger values of this measurement, linked to a wide body shape which would include a large trunk. However, it has been recently observed that to fully account for the 3D thorax morphology, not only the ribs but also the thoracic vertebrae should be considered (Bastir et al, ; García‐Martínez, ; García‐Martínez et al, ). This is because the orientation of the transverse processes of the thoracic vertebrae could play an important role regarding the orientation of the ribs and the mediolateral amplitude of the thorax.…”
Section: Discussionmentioning
confidence: 99%
“…This is also due to the fact that 3D rib cage morphology can only be understood as the result of the sum of its metameric components: ribs and vertebrae (Bastir et al, ; García‐Martínez, ; García‐Martínez et al, ). Moreover, besides these technical limitations, researchers have paid more attention to the quantification of the thorax variability in fossil hominin species than in the study of modern human thoracic variability (Bastir et al, ; Chapman et al, ; Franciscus and Churchill, ; Gómez‐Olivencia, ; Gómez‐Olivencia et al, ; García‐Martínez et al, ; Latimer, Lovejoy, Spurlock, & Haile‐Selassie, ; Schmid, ; Schmid et al, ; Williams et al, ). Although one study included a cold‐adapted population, it was used as a comparative sample for addressing the possible cold‐adaptation in the Neanderthal Kebara 2 thorax (Gómez‐Olivencia et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations